Parents' perspectives on children's mental health during online learning during the Covid-19 pandemic - Ari Rosita Putri; Julia Julia (Psychology, Evaluation, and Technology in Educational Research, 2022)
Online learning indirectly has an impact on children's mental health, whereas, in situations like this, learning activities are carried out face-to-face, which requires children to continue to deal with screens/monitors. This study aims to explore information on parents' views on children's mental health during online learning. The research method used is qualitative research with a case study design. The research participants were 10 parents of students who were in the Cirebon, Indramayu, and Majalengka areas with an age range of 25-42 years. The data collection technique used a survey in the form of an open-ended question. The results of data collection and analysis are presented in several themes. The results showed that parents saw that their children's mental health during the pandemic decreased slightly due to several factors such as unstable internet access, many school assignments, and staring at screens with laptops all day without doing other activities.